Chitosan films incorporated with Thymus capitatus essential oil: mechanical properties and antimicrobial activity against degradative bacterial species isolated from tuna (Thunnus sp.) and swordfish (Xiphias gladius) - Grande-Tovar, Carlos David (J Food Sci Technol, 2018)
Chitosan-based coatings and films have been widely studied, demonstrating to be an efficient and eco-friendly approach to extend the shelf life of food products. The effect of incorporating Thymus capitatus essential oil (TCEO) at different concentrations (0.5, 1.0, and 1.5% w/w) on physical, mechanical and antimicrobial properties of chitosan films was studied. The antimicrobial activity of the films was evaluated by agar diffusion method, against 23 spoiling microorganisms isolated from tuna and swordfish (ten Shewanella baltica, one S. morhuae, one S. putrefaciens, two Pseudomonas fluorescens, two P. fragi, five Serratia spp., one Aeromonas molluscorum, and one Acinetobacter radioresistens) and Shewanella putrefaciens ATCC 49138. The films exerted antimicrobial activity against all the tested strain, although not proportional to increasing TCEO concentration. In particular, S. baltica was the most sensitive species and the inhibition was stable after 72 h. In general, TCEO incorporation in chitosan films, significantly (p < 0.05) decreased the water permeability (from 0.577 ± 0.060 gmm/kPahm(2) at 61% R.U. for chitosan to 0.487 ± 0.037 gmm/kPahm(2) for the film with 1.5% TCEO), the elongation at brake (from 27.322 ± 2.35% for chitosan to 14.695 ± 3.99% for the film with 1.5% TCEO) and increased the tensile strength (from 1.697 ± 0.16% for chitosan to 19.480 ± 2.86% for the film with 1.5% TCEO). Moisture content and water contact angle of the films also showed a similar trend with TCEO introduction, because of crosslinking reaction among the polymer chains and TCEO components. Scanning electron microscopy confirmed structure-properties relationships. These results suggest chitosan films incorporated with TCEO as an alternative treatment to inhibit the growth of degradative bacteria with potential application in the fish industry. The importance of testing more than one strain of the same bacteria species to evaluate the effectiveness of chitosan-essential oils coatings was also demonstrated.